Mesophyll conductance and N allocation co-explained the variation in photosynthesis in two canola genotypes under contrasting nitrogen supply - Liu, Jiahuan; Zhang, Kangkang; Bi, Junguo; Yu, Xinqiao; Luo, Lijun; Hu, Liyong (Frontiers in Plant Science, 2023)
The application of nitrogen fertilizer within a normal range has been found to increase the leaf nitrogen content and photosynthetic rate of canola plants (Brassica napus L.). Despite numerous studies on the separate effects of CO2 diffusion limitation and nitrogen allocation trade-off on photosynthetic rate, few have examined both these factors in relation to the photosynthetic rate of canola. In this study, two genotypes of canola with varying leaf nitrogen content were analyzed to determine the impact of nitrogen supply on leaf photosynthesis, mesophyll conductance, and nitrogen partitioning. The results showed that the CO2 assimilation rate (A), mesophyll conductance (gm), and photosynthetic nitrogen content (Npsn) increased with an increase in nitrogen supply in both genotypes. The relationship between nitrogen content and A followed a linear-plateau regression, while A had linear relationships with both photosynthetic nitrogen content and gm, indicating that the key to enhancing A is increasing the distribution of leaf nitrogen into the photosynthetic apparatus and gm, rather than just increasing nitrogen content. Under high nitrogen treatment, the genotype (QZ) with high nitrogen content had 50.7% more nitrogen than the other genotype (ZY21), but had similar A, which was primarily due to ZY21's higher photosynthetic nitrogen distribution ratio and stomatal conductance (gsw). On the other hand, QZ showed a higher A than ZY21 under low nitrogen treatment as QZ had higher Npsn and gm compared to ZY21. Our results indicate that, in selecting high PNUE rapeseed varieties, it is important to consider the higher photosynthetic nitrogen distribution ratio and CO2 diffusion conductance.